The crystal structure of a natural DNA polymerase complexed with mirror DNA. Issue 14 (23rd January 2020) - An, Jinsu; Choi, Jaewoo; Hwang, Dohyeon; Park, Jihyun; Pemble, Charles W.; Duong, Thi Hoai Men; Kim, Kyoung-Ran; Ahn, Heechul; Chung, Hak Suk; Ahn, Dae-Ro
Abstract : The intrinsic l -DNA binding properties of a natural DNA polymerase was discovered. Abstract : The intrinsic l -DNA binding properties of a natural DNA polymerase was discovered. The binding affinity of Dpo4 polymerase for l -DNA was comparable to that for d -DNA. The crystal structure of Dpo4/l -DNA complex revealed a dimer formed by the little finger domain that provides a binding site for l -DNA.